Current Issues of Evaluating the Effectiveness of Public Procurement - PRODANOVA, Natalia Alekseevna (2021)
Public procurement under the contract system plays an important role in the development of the country's economy. The volume of state ownership and the volume of public procurement are impressive in their scale. Within the framework of the contract system, one of the priority goals is to increase the efficiency of state and municipal procurement. This article analyzes the existing indicators of the effectiveness of state and municipal procurement and provides recommendations for expanding the range of these indicators.